Effectiveness of Sugarcane Bagasse Adsorbents for Chromium Removal from Industrial Metal Plating Wastewater - Nabila, Iffah; Rachmawati, Siti; Masykuri, Mohammad; Nurlita, Siti (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2026)
Wastewater from metal plating businesses contains hazardous heavy metals, including chromium (Cr), which must be properly treated to avoid environmental contamination. Adsorption utilizing natural materials, such as sugarcane bagasse, is a promising option. This study compared the effectiveness of H2SO4-activated sugarcane bagasse with sugarcane bagasse-based activated carbon in removing total chromium (Cr-T) from metal plating wastewater and analyzed the effects of adsorbent mass and contact time. Atomic absorption spectrophotometry (AAS) was used to measure the final chromium concentrations after batch adsorption was conducted with different masses and contact periods. The findings revealed that the adsorption effectiveness increased as the adsorbent mass and contact duration increased, reaching an ideal point. While activated carbon achieved its peak at 12 g and 120 min (95% and 47.6% efficacy, respectively), activated bagasse performed best at 15 g and 150 min (51.9% and 43% effectiveness, respectively). Activated carbon performed better because of its increased surface area and pore structure resulting from carbonization. These results demonstrate that sugarcane bagasse is a potential, affordable, and sustainable natural adsorbent for lowering total chromium in industrial effluents, particularly when transformed into activated carbon.